Implementasi Syariat Islam: Telaah atas Praktik Ijtihad Umar bin Khattab - Muhammad Ridwan (TSAQAFAH, 2017)
The reason of writing this article is the problem and mistake come from the contemporary Muslim thinkers who made mas}lah}at as the only benchmark in Islamic law, they even assumed that mas}lah}at is more important than the sharia itself. From this they concluded that deconstructing sharia based on mas}lah}at is permissible. They built their argument on the basis of the ijtihâd done by ‘Umar bin Khattab. At that time, ‘Umar broke the law of hand cuts for theft, stoped giving zakat for the converts, and did not give the spoils land to the soldiers. In fact, according to contemporary Muslim thinkers, these three things have been determined in the Qur’an and Sunnah of the Prophet SAW. It means ‘Umar bin Khattab’s ijtihâd is a breakthrough in liberal thinking. ‘Umar dared to contrary what was established in the Qur’an and the hadith of the Prophet. Then, ‘Umar is regarded as a fgure who has applied hermeneutic methods in Islamic law. This thought actually is a mistake. The contemporary thinkers only thought partially and did not discuss ‘Umar’s ijtihâd thoroughly and deeply. By referring to earlier Muslim scholars, this article try to prove that ‘Umar’ ijtihâd is an attempt to implement the Islamic Shari’a, despite elimiting or dismissing Islamic Shari’a itself as the above thinkers claim.